Land Conflicts: Mapping Obstacles and Sustainable Solutions - Citra Darminto; Syamsir Syamsir; Michael Lega; Tri Imam Munandar (School of Postgraduate Studies, Diponegoro Univer, 2025)
Land conflicts in Indonesia, especially in Jambi Province, have become an urgent issue affecting the ownership and management of agricultural land, forests and natural resources. This problem involves various parties and requires serious handling to reduce social tensions, increase justice, and ensure environmental sustainability. This research aims to explore trends, obstacles, and adaptive solutions in resolving land conflicts in Jambi Province, Indonesia. The research method used is qualitative, involving data collection stages through interviews, observation, and documentation of land conflict cases from various official sources. Nvivo 12 Plus was also used in this study to help code the data. The research findings highlight the complexity and escalation of the urgency of land conflicts in Jambi Province, which are widespread in the plantation and forestry sectors involving a large number of companies in various industrial sectors. The main obstacles faced in resolving conflicts include social tensions, legal uncertainty, lack of coordination, limited resources, lack of public awareness, rapid economic growth, and policy complexity. To overcome this challenge, adaptive and sustainable steps are needed, including strengthening the legal framework, increasing coordination between institutions, and community participation through inclusive dialogue. In addition, human rights and justice-based approaches are integrated to support sustainable conflict resolution while strengthening local capacity to be actively involved in the conflict resolution process. This research provides important insights for future policymakers, researchers, and practitioners. This research also provides important insights for formulating more effective and sustainable policies in dealing with land conflicts in Jambi Province, by integrating approaches based on human rights, justice and community participation.